(untitled) (Research, Society and Development, 2020)
The reprocessing of antiseptic oiler plastic bottles is a common practice in several hospitals, yet there is no scientific recommendation son how to perform it. Therefore, this study aimed to evaluate the conformities and non-conformities that involve the reprocessing of the oilers, and to compare the benefit cost of the reprocessed bottles in relation to the disposable ones. The research was of the descriptive observational type, and analyzed the weekly reprocessing of 26 oilers in a surgical unit. Based on Avedis Donabedian’s health quality management model, structural and procedural problems were observed, such as: rusty shelves, lack of Personal Protective Equipment (PPE), absence of cleaning brushes, improperly stored material, lack of professional technical knowledge, among others. The volume of wasted solutions, used materials and the professional’s time spent on the task were considered, reaching the conclusion that disposable oilers have a higher benefit cost than reprocessed ones, in addition to important failures related to the process that affect patient safety.